Why Do Men Accumulate Abdominal Visceral Fat? - Nauli, Andromeda M.; Matin, Sahar (Frontiers in Physiology, 2019)
Men have a higher tendency to accumulate abdominal visceral fat compared to pre-menopausal women. The accumulation of abdominal visceral fat in men, which is a strong independent predictor of mortality, is mainly due to the higher dietary fat uptake by their abdominal visceral fat. Since dietary fat is absorbed by the enterocytes and transported to the circulation in the forms of chylomicrons and very low-density lipoproteins (VLDLs), it is crucial to understand how these lipoproteins are different between men and women. The chylomicrons in men are generally bigger in size and more in quantity than those in women. During the postprandial state, these chylomicrons congest the lamina propria and the low-pressure lymphatics. In this paper, we propose that this congestion predisposes the chylomicron triglycerides to hydrolysis by lipoprotein lipase (LPL). The liberated fatty acids are then stored by the nearby abdominal visceral adipocytes, leading to the accumulation of abdominal visceral fat. These mechanisms perhaps explain why men, through their bigger and higher production of chylomicrons, are more likely to accumulate abdominal visceral fat than pre-menopausal women. This accumulation eventually leads to belly enlargement, which confers men their apple-shaped body.